Literature Review on Nutritional Status and 25-Meter Swimming Speed among Prospective Students in the Context of Police Academy Preparation - Yulianti, Bella; Wahyuri, Asep Sujana; Bafirman, Bafirman (STKIP Singkawang, 2024)
Physical health and fitness are crucial aspects in preparing for entry into the Indonesian National Police (Polri). Swimming, as a sport requiring physical fitness and technical skills, is a primary focus in this preparation. This study aims to explore the relationship between nutritional status and 25-meter swimming speed among prospective students preparing to enter Polri. The method employed is a literature review. Literature review is a research design used to gather data sources related to a topic, describing core content based on acquired information. Data collection for the literature review was conducted using database search tools, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The study analyzed journals and summarized statements relevant to the research objectives. Journal search procedures adhered to PICOT criteria. The analysis results indicate a positive relationship between good nutritional status and swimming speed. Factors such as balanced body composition and adequate nutritional intake play critical roles in enhancing swimming performance. The implications of these findings underscore the need for greater attention to nutritional aspects in swimming training programs and physical preparation for prospective Polri members. Emphasizing monitoring and improving nutritional status in swimming training programs can significantly benefit prospective Polri members in achieving optimal physical fitness. Further research is necessary to better understand the mechanisms linking nutritional status and swimming speed, and to develop effective intervention strategies for enhancing swimming performance